2020
DOI: 10.3390/su12083353
|View full text |Cite
|
Sign up to set email alerts
|

Growth Characteristics and Anti-Wind Erosion Ability of Three Tropical Foredune Pioneer Species for Sand Dune Stabilization

Abstract: Rainstorms frequently cause runoff and then the runoff carries large amounts of sediments (sand, clay, and silt) from upstream and deposit them on different landforms (coast, plain, lowland, piedmont, etc.). Afterwards, monsoons and tropical cyclones often induce severe coastal erosion and dust storms in Taiwan. Ipomoea pes-caprae (a vine), Spinifex littoreus (a grass), and Vitex rotundifolia (a shrub) are indigenous foredune pioneer species. These species have the potential to restore coastal dune vegetation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…Statistical data demonstrated that the maximal root pullout resistance of C. dactylon is remarkably higher than that of E. ophiuroides. Earlier studies also demonstrated positive relations between pullout resistance, root biomass, architecture, and root surface area [30,39,43]. Clearly, C. dactylon with more profuse fibrous roots, root biomass and total root surface has higher pullout resistance than E. ophiuroides.…”
Section: Root Pullout Resistancementioning
confidence: 78%
See 1 more Smart Citation
“…Statistical data demonstrated that the maximal root pullout resistance of C. dactylon is remarkably higher than that of E. ophiuroides. Earlier studies also demonstrated positive relations between pullout resistance, root biomass, architecture, and root surface area [30,39,43]. Clearly, C. dactylon with more profuse fibrous roots, root biomass and total root surface has higher pullout resistance than E. ophiuroides.…”
Section: Root Pullout Resistancementioning
confidence: 78%
“…Root surface area and length were evaluated utilizing WinRHIZO software (Regent Inc., Quebec, QC, Canada) [28], while root volume was estimated using water displacement technique [29]. Root dry unit weight was also measured [30]. These figures were used to determine root traits.…”
Section: Growth Traitsmentioning
confidence: 99%
“…But for the urban remnant vegetation, especially the herb-layer plant with high urban disturbance, are more necessary to study how they can survive. Pioneer plants, for example, are hardy species that are the first to colonize previously disrupted or damaged ecosystems (Lee et al 2020). In urban, Pioneer plants, mainly weeds and annual herbaceous plants, are often able to withstand high air pollution, trampling, alkaline, compacted, and nitrogen-rich soils those are generated by the high degree of urbanization (McKinney 2006), so they are easily replaced by late-successional species in the later period.…”
Section: Introductionmentioning
confidence: 99%
“…In northern Bangladesh, traditional erosion management approaches have been applied to control riverbank erosion and enhance livelihood resilience [10]. The estuarine vegetation is very efficient at trapping drifting sand and reducing aeolian erosion [11], and its use is regarded as an effective ecological engineering method for sand drift control [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Hamidifar et al [24] demonstrated that vetiver grass (Vetiveria zizanioides L.) can increase soil cohesion and the soil internal friction factor and enhance riverbank shear strength. Several studies revealed that plant coverage can notably decrease the wind erosion rate [13,25]. However, the root traits, mechanical properties and wind erosion resistance of A. formosana, P. australis and S. spontaneum have not been explored.…”
Section: Introductionmentioning
confidence: 99%